Metagenomic Analysis of Bacterial Community in the Gut of Blister Beetle Mylabris pustulata Thunberg - Achmad Dinoto; Zahra Noviana; Oscar Efendy; Heddy Julistiono (Institute for Research and Community Services (LPPM) ITB, 2022)
Blister beetles are an important object of study in the field of agriculture and health. Despite being known to be important for the host animal, the gut bacteria of blister beetles have not been investigated deeply. This study aimed to provide the first initial description of the gut bacterial community of Mylabris pustulata as one species of blister beetles, based on a culture-independent technique. Adult blister beetles of the same colony were sampled and confirmed as Mylabris pustulata Thunberg. The gut content was used in high throughput sequencing, targeting the V3-V4 regions of 16S rRNA gene, and in the cultivation of resident bacteria. The results showed that higher bacterial richness was present in the gut communities when compared to the grown bacterial culture. Proteobacteria was confirmed as the most abundant phylum in the gut of M. pustulata, whereby most reads belonged to the class of Gammaproteobacteria. The dominant bacterial genera were determined as Enterobacter, Acinetobacter, Enterococcus, Klebsiella, and Pseudomonas. In addition, our cultivation attempts led to successful isolation of members of Klebsiella and Enterococcus. The subject of this study could be explored further to find the potential roles of these microbiota in the gut of the specific beetles and their bioprospects.